PENGARUH KECEPATAN POTONG TERHADAP UMUR PAHAT BOR PADA BENCH DRILL IXION BT 25 MENGGUNAKAN CAIRAN PENDINGIN - Kevin Lorenzo; I Nyoman Gede; Rudy Poeng (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2022)
This study discusses how to determine the life of the drill chisel in the process of cutting workpieces using coolant and whether the cutting speed will affect the life of the chisel on the IXION BT 25 bench drill machine. The purpose of this study was to analyze the age of the chisel by varying the cutting speed and conducting linear regression analysis to determine the effect of cutting speed on the chisel life of the IXION BT 25 bench drill machine.The test results of the drill process on bench drill IXION BT 25 that has been developed using coolant obtained the first point cutting speed of 28,903 m / minute resulting in a chisel life of 0.019 minutes, the second point cutting speed of 29,908 m / minute resulting in a chisel life of 0.058 minutes and the third point cutting speed of 30,159 m / minute resulting in a chisel life of 0.108 minutes. From these results it is seen that the life of the chisel in the drill process using coolant will be increased by increasing the cutting speed. The results of linear regression analysis obtained by Y=-1.7697+0.0617X, this shows that the effect of cutting speed on the chisel life of the test results conducted on ixion BT 25 bench drill machines that have been developed using coolant that is each cutting speed increased by 1 m / minute will decrease the chisel life by 0.0617 minutes.Â Keywords: Cutting Speed, Chisel Life, IXION BT 25 bench drill machine